Response to COVID-19: building resilience through water and wastewater management in Ghana - Darteh, Bertha; Cofie, Olufunke O.; Nikiema, Josiane; Mapedza, Everisto D.; Gebrezgabher, Solomie A.; Okem, Andrew Emmanuel (IWA Publishing, 2023)
This study assessed the effects of COVID-19 on Ghana’s WASH system. It focused on low-income households and WASH sector stakeholders using Ayawaso East Municipality as a case study to document lessons from the pandemic’s impact on the WASH sector. We used the water and sanitation system approach to understand the effects of COVID-19 mitigation measures on the WASH system. Data were collected through surveys, stakeholder engagements, and document analysis. We found that the government’s WASH response increased hygiene practices, solid and liquid waste generation, and water consumption. Sanitation service providers experienced reduced demands for their services, lost clients, and increased operational expenditure. The pandemic’s impact is gendered, with women and girls experiencing a greater burden. We argue that responses to the pandemic highlight the need and opportunities for sustainable management of sanitation waste through integrated, circular economy business models, turning waste into valuable resources. Responses to COVID-19 in the WASH system are multisectoral because of its interconnected nature, highlighting the need to integrate sectors beyond water and sanitation. This requires improved institutional structures, policies, investment, and professionalising service providers.